2019
DOI: 10.1097/prs.0000000000006069
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Application of Botulinum Toxin Type A Prevents Hypertrophic Scarring after Epicanthoplasty: A Split-Face, Double-Blind, Randomized Trial

Abstract: Background: Postoperative hypertrophic scarring of the medial canthal area is a common phenomenon and deterrent for patients considering epicanthoplasty. Botulinum toxin type A has been reported for hypertrophic scar and keloid treatment. However, there is a lack of high-level evidence regarding the effects of botulinum toxin type A in the medial canthal area. Methods: In this split-face, double-blind, randomized trial, 43 consecutive consenting patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…Among these removed studies, 5 were conducted on animals; 3 were letters; 4 were reviews; 4 lacked a control group; 2 were case reports; and 3 had incomplete data. Finally, 12 studies [12][13][14][15][16][17][18][19][20][21][22][23] involving 497 cases (372 patients) were identified and included in the meta-analysis ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these removed studies, 5 were conducted on animals; 3 were letters; 4 were reviews; 4 lacked a control group; 2 were case reports; and 3 had incomplete data. Finally, 12 studies [12][13][14][15][16][17][18][19][20][21][22][23] involving 497 cases (372 patients) were identified and included in the meta-analysis ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…These studies were conducted in patients from several different countries, as shown in Table 1. Ten studies compared a BTXA group with a saline group, [12][13][14][15][17][18][19][20][21]23 and 2 studies compared a BTXA group with a blank control group. 16,22 Several different types of BTXA products were reported, as shown in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations